Development of compositional thinking of future specialists in creativity - Baidabekov, Әуез; Karabalin , Ораз (Рroblems of engineering and professional education, 2023)
The article considers the importance of compositional thinking of students in the work of project activities. Particular attention is paid to the influence of the composite solution in the organization of project work using skills and abilities. Compositional skills help to find an artistic image of the object, to form and improve compositional thinking. The development of the qualities of the future designer, both specialist and professional, involves the formation of his General culture. This process allows them to consolidate their skills, associate theory with practice and develop professional skills through the implementation of the studied special disciplines and assigned tasks. To solve these problems, students characterize the development of compositional thinking in the performance of experimental works of formal composition as one of the effective means of project activity.